Leveraging hallmark Alzheimer’s molecular targets using phytoconstituents: Current perspective and emerging trends - Prajakta A. Dhage (17302789) (2021)
Alzheimer's disease (AD), a type of dementia, severely distresses different brain regions. Characterized by various neuropathologies, it interferes with cognitive functions and neuropsychiatrical controls. This progressive deterioration has negative impacts not only on an individual's daily activity but also on social and occupational life. The pharmacological approach has always remained in the limelight for the treatment of AD. However, this approach is condemned with several side effects. Henceforth, a change in treatment approach has become crucial. Plant-based natural products are garnering special attention due to lesser side effects associated with their use. The current review emphasizes the anti-AD properties of phytoconstituents, throws light on those under clinical trials, and compiles information on their specific mode of actions against AD-related different neuropathologies. The phytoconstituents alone or in combinations will surely help discover new potent drugs for the effective treatment of AD with lesser side effects than the currently available pharmacological treatment. Other Information Published in: Biomedicine & Pharmacotherapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biopha.2021.111634